Uncertainty quantification for severe-accident reactor modelling: Results and conclusions of the MUSA reactor applications work package - S. Brumm; F. Gabrielli; V. Sanchez Espinoza; A. Stakhanova; P. Groudev; P. Petrova; P. Vryashkova; P. Ou; W. Zhang; A. Malkhasyan; L.E. Herranz; R. Iglesias Ferrer; et al. (Annals of Nuclear Energy, 2025)

Multi-stage ultrahigh temperature metamorphism in the lower crust of the Kaapvaal craton recorded by U–Pb ages of garnet - Q. Shu; A. Beranoaguirre; R. Albert; L. J. Millonig; J. B. Walters; H. R. Marschall; A. Gerdes; H. E. Hoefer; D. Hezel; G. P. Brey (Contributions to Mineralogy and Petrology, 2024)
U–Pb ages were determined by split-stream LA-SF/MC-ICPMS in garnets from UHT granulite xenoliths (Star mine, South Africa; 124 Ma). They give a considerable age range of 400 million years with well-defined maximas at 3.09, 3.01 and 2.75 Ga. The oldest peak overlaps with the changeover from tonalites to K-granites at 3.14–3.04 Ga and with zircon ages of the mid-crustal granulites of the Vredefort dome (3.1 Ga) in the wake of the 3.2 Ga collision of three terrains that compose the Witwatersrand block. Subduction (or sagduction) of the uppermost crust in an ultrahot orogen setting brought shales and greenstones to the lower crust. Ultrahigh temperature (UHT) conditions are the result of high mantle potential temperatures and self- heating by the radioactive inventory of the subducted lithologies. Metamorphism, anatexis to very high degrees and melt extraction left UHT granulites as residue. Rejuvenation of UHT conditions was brought about by Dominion Group magmatism between 3.0 and 2.95 Ga. Magmatic uprise caused intense shearing in the lower crust followed by recrystallisation of the shear zones to generate the younger garnet age group. Ventersdorp flood basalt volcanism caused similar processes at around 2.72 Ga and generated the third garnet age group. Zircon gives U–Pb ages mainly around 2.72 Ga (both literature and our own data) i.e. zircon adjusted or newly crystallized at the youngest UHT event. Only few zircon grains retained older ages up to 2.94 Ga. Still unconstrained, but very high closure temperatures (≥ 1100 °C) for the U–Pb system in garnet keep the memory of the oldest ages in UHT granulites. Such ages can only be reset by recrystallization. This way, garnet records a prolonged high-temperature history of the lower crust of the Kaapvaal craton.

Uncertainty and sensitivity analysis of the ASTEC simulations results of a MBLOCA scenario in a generic KONVOI plant using the FSTC tool - A. Stakhanova; F. Gabrielli; V.H. Sanchez-Espinoza; A. Hoefer; E.M. Pauli (Annals of Nuclear Energy, 2023)

Application of the MOCABA algorithm and the FSTC tool for source term predictions during severe accident scenarios - A. Stakhanova; F. Gabrielli; V.H. Sanchez-Espinoza; A. Hoefer; E.M. Pauli (Annals of Nuclear Energy, 2023)

Improved detection of fluorescently labeled microspheres and vessel architecture with an imaging cryomicrotome - Pepijn van Horssen; Maria Siebes; Imo Hoefer; Jos A. E. Spaan; Jeroen P. H. M. van den Wijngaard (Medical & Biological Engineering & Computing, 2010)

Carbachol activates a K+ channel of very small conductance in the basolateral membrane of rat pancreatic acinar cells - M. Köttgen; A. Hoefer; S. Kim; U. Beschorner; R. Schreiber; M. Hug; R. Greger (Pflügers Archiv - European Journal of Physiology, 1999)

Carbachol activates a K + channel of very small conductance in the basolateral membrane of rat pancreatic acinar cells - M. Köttgen; A. Hoefer; Kim S.; U. Beschorner; R. Schreiber; Hug M.; R. Greger (Pflügers Archiv - European Journal of Physiology, 1999)

Mutations in the SIV env and the M13 lacZa gene generatedin vitro by reverse transcriptases and DNA polymerases - A. W. Stuke; O. Ahmad-Omar; K. Hoefer; G. Hunsmann; K. D. Jentsch (Archives of Virology, 1997)